Transient elastography compared to serum markers to predict liver fibrosis in a cohort of Chinese patients with chronic hepatitis B. Issue 4 (April 2015) - Jia, Jidong; Hou, Jinlin; Ding, Huiguo; Chen, Guofeng; Xie, Qing; Wang, Yuming; Zeng, Minde; Zhao, Jingmin; Wang, Tailing; Hu, Xiqi; Schuppan, D.
Abstract: Background and Aim: Liver stiffness measurement (LSM) using transient elastography (FibroScan) is a useful tool to assess fibrosis in various chronic liver diseases. However, studies were mainly performed in Western countries and largely focused on chronic hepatitis C (CHC). We therefore carried out a multicenter study to validate the accuracy of LSM in the assessment of liver fibrosis in a large cohort of Chinese patients with chronic hepatitis B (CHB). Methods: We compared LSM results to histological staging and serum fibrosis markers (five direct markers, APRI and FIB‐4) using Spearman correlation analysis and area under receiver operating characteristic (ROC) curves (AUROCs). Results: Four hundred sixty‐nine patients were enrolled and eligible for statistical analysis. LSM in F0 to F4 was 5.5 ± 1.7, 5.8 ± 2.2, 7.6 ± 3.4, 14.5 ± 10.8, and 22.3 ± 13.6 kPa, respectively (correlation with fibrosis stage r = 0.522, P < 0.001). AUROC for LSM to correctly allocate patients to histological fibrosis stage ≥ F2, ≥ F3, and F4 was 0.82, 0.88, and 0.90, respectively. LSM outperformed serum fibrosis markers for detection of fibrosis F ≥ 2 and F4. Patients with ALT levels 1–5x and > 5x the upper limit of normal values had significantly higher stiffness values than stage‐matched patients with normal alanine aminotransferase. Conclusion: Transient elastography is a reliable noninvasive technique to predict significant liver fibrosis in Chinese patients with CHB, being superior to current biomarker panels. However, enhanced inflammatory activity can lead to elevated stiffness values unrelated to histological fibrosis stage.